2014
DOI: 10.1186/s12870-014-0254-y
|View full text |Cite
|
Sign up to set email alerts
|

Phosphite-induced changes of the transcriptome and secretome in Solanum tuberosum leading to resistance against Phytophthora infestans

Abstract: BackgroundPotato late blight caused by the oomycete pathogen Phytophthora infestans can lead to immense yield loss. We investigated the transcriptome of Solanum tubersoum (cv. Desiree) and characterized the secretome by quantitative proteomics after foliar application of the protective agent phosphite. We also studied the distribution of phosphite in planta after application and tested transgenic potato lines with impaired in salicylic and jasmonic acid signaling.ResultsPhosphite had a rapid and transient effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 78 publications
1
54
1
3
Order By: Relevance
“…In potato it has been reported that phosphite leads to excessive accumulation of hydrogen peroxide and PR1 transcripts [80], which is associated with SA signaling. A time-course study of phosphite applications in potato by genome-wide microarrays did not detect up-regulation of PR1 transcripts, even if phosphite caused a major, but transient, change of the transcriptome within 24 h [75]. Instead, genes associated with defense, wounding and oxidative stress were found to constitute the core of the phosphite response, together with changes in primary metabolism and cell wall-related processes.…”
Section: Induced Resistance Mechanisms In Solanaceaementioning
confidence: 99%
See 1 more Smart Citation
“…In potato it has been reported that phosphite leads to excessive accumulation of hydrogen peroxide and PR1 transcripts [80], which is associated with SA signaling. A time-course study of phosphite applications in potato by genome-wide microarrays did not detect up-regulation of PR1 transcripts, even if phosphite caused a major, but transient, change of the transcriptome within 24 h [75]. Instead, genes associated with defense, wounding and oxidative stress were found to constitute the core of the phosphite response, together with changes in primary metabolism and cell wall-related processes.…”
Section: Induced Resistance Mechanisms In Solanaceaementioning
confidence: 99%
“…Instead, genes associated with defense, wounding and oxidative stress were found to constitute the core of the phosphite response, together with changes in primary metabolism and cell wall-related processes. Interestingly, there was an overlap of 40% between phosphite- and BABA-regulated transcripts, indicating that similar processes are affected upon induction of resistance even though the effect of BABA on the transcriptome lasts longer and goes on for at least 48 h [11,75]. In a study of soluble proteins from potato leaves treated with the phosphite product Confine™, Lim et al [77] found increased abundance of proteins involved in SA-dependent defense responses, reactive oxygen species (ROS) and calcium-dependent pathways, whereas proteins involved in amino acid and starch metabolism were down-regulated.…”
Section: Induced Resistance Mechanisms In Solanaceaementioning
confidence: 99%
“…Этот ресурс Европейского института биоинформатики содержит результаты 77 экс периментов по анализу экспрессии генов картофеля (Ali et al, 2014;Burra et al, 2014). Основные типы экспери ментов, данные по которым опубликованы в ArrayExpress для S. tuberosum, это высокопроизводительное секвени рование транскриптома ('RNAseq of coding RNA', 9 экс периментов) и анализ экспрессии с помощью микрочипов ('transcription profiling by array', 62 эксперимента).…”
Section: транскриптомные исследования как ключ к пониманию механизмовunclassified
“…Although several studies have reported the negative effects of Phi on the growth of plants [64]- [69], its mode of action at the molecular level is not fully understood [23] [70]. Even though the proteomic analysis [9], transcriptomic profiling [24] and high-performance ion chromatography (HPIC) method [10] have been used for assessing the accumulation of Phi in potato tubers, a detailed study of metabolite changes in response to Phi can increase our understanding of plant defense responses, interactions between metabolic networks and basic plant metabolism. Metabolomics is a powerful approach to gain a comprehensive perspective of how metabolic networks are regulated and has increasingly been applied by many researchers in recent years.…”
Section: Sugar and Sugar Alcohol Changes From Different Treatment Groupsmentioning
confidence: 99%
“…Lovatt and Mikkelsen [63] also reported that Phi may influence sugar metabolism, cause internal hormonal and chemical changes, and induce the SA pathway, resulting in increased floral intensity, and fruit yield and quality in various crops including onions, potatoes and tomatoes. Burra et al [24] investigated transcriptome analysis of potatoes after Phi treatment and found that transcripts associated with defense, wounding, and oxidative stress constituted the core of the Phi response. They also observed changes in primary metabolism and cell wall related processes.…”
Section: Sugar and Sugar Alcohol Changes From Different Treatment Groupsmentioning
confidence: 99%